A Role for Neuregulin-1 in Promoting Keloid Fibroblast Migration via ErbB2-mediated Signaling - Natalie Jumper; Tom Hodgkinson; Ralf Paus; Ardeshir Bayat (Medical Journals Sweden, 2017)
Keloid disease is a fibroproliferative tumour characterised by aggressive local invasion, evident from a clinically and histologically active migrating margin. During combined laser capture microdissection and microarray analysis-based in situ gene expression profiling, we identified upregulation of the polypeptide growth factor neuregulin-1 (NRG1) and ErbB2 oncogene in keloid margin dermis, leading to the hypothesis that NRG1 contributed to keloid margin migration through ErbB2-mediated signalling. The aim of this study was to probe this hypothesis through functional in vitro studies. Exogenous NRG1 addition to keloid and normal skin fibroblasts altered cytokine expression profiles, significantly increased in vitro migration and keloid fibroblast Src and protein tyrosine kinase 2 (PTK2/FAK) gene expression. ErbB2 siRNA knockdown attenuated both keloid fibroblast migration and Src/PTK2 expression, which were not recovered following NRG1 administration, suggesting the NRG1/ErbB2/Src/PTK2 signaling pathway may be a novel regulator of keloid fibroblast migration, and representing a potential new therapeutic target.